Mothering Death: A Psychosocial Interpretation of Breast Cancer Biography - Birgitta Haga Gripsrud (Qualitative Studies, 2021)
In this article I take as my point of departure a puzzle presented by a woman who had an apparently ‘bizarre’ reaction to a breast cancer diagnosis. In the clinic, she had exclaimed: “I would rather die than lose the breast!”. My aim is to unpack layers in this woman’s embodied and enculturated experience, with a view towards developing a psychosocial interpretation of breast cancer biography. The single case on which the present study is based, was extracted from a larger longitudinal data set which allowed me to follow ‘Ella’s’ transition from diagnosis to survivorship. I relied on five sources of data to unfold the case: two participant-generated texts (expressive writing and a Breast Biography), two interviews, and my own field notes. The two texts that Ella wrote provided a participant-led frame for depth-hermeneutic group interpretation sessions, the first of which, synergistically, produced a scenic voicing of latent content in the sub-text of Ella’s expressive writing: the fantasy of mothering death. This subsequently became a lead for my further interpretation of the case, and for methodological reflections on the value of shared thinking in qualitative data interpretation. Crucially, and with some bearing on the current healthcare context, this interpretive study sheds light on what goes on beneath the surface of an apparently ‘irrational’ and ‘recalcitrant’ patient, evidenced by Ella’s entry into what I call a ‘vortex of suffering’. Findings point towards her suffering as an expression of a psychosocial reality, against the backdrop of hope and ideals contained within a psychosocial imaginary that revolves around biomedical cure and reparation.